A Novel Oxidative Stress Mediator in Acute Appendicitis: Thiol/Disulphide Homeostasis. (23rd August 2016) - Ozyazici, Sefa; Karateke, Faruk; Turan, Umit; Kuvvetli, Adnan; Kilavuz, Huseyin; Karakaya, Burak; Ozaltun, Pınar; Alısık, Murat; Erel, Ozcan
Abstract : Aim . To investigate the role of a novel oxidative stress marker, thiol/disulphide homeostasis, in patients diagnosed with acute appendicitis (AA). Methods . In this study, seventy-one (43 male and 28 female) patients diagnosed with AA and 71 (30 male and 41 female) healthy volunteers were included. Age, gender, body mass index (BMI), haemoglobin (Hb), white blood cell (WBC), c-reactive protein (CRP), and thiol/disulphide homeostasis parameters (native thiol, total thiol, disulphide, disulphide/native thiol, native thiol/total thiol, and disulphide/total thiol ratios) were compared between the groups. Thiol/disulphide homeostasis was determined by a newly developed method by Erel and Neselioglu. Results . The native thiol, total thiol, and the native thiol/total thiol ratio levels were statistically significantly decreased in the AA compared with the control group (p < 0.001 ). Disulphide level and the ratios of disulphide/native thiol and disulphide/total thiol were higher in the AA group than in the control group (p < 0.001 ). There was a negative correlation of CRP with native thiol, total thiol, and native thiol/total thiol ratio while there was a positive correlation of CRP with disulphide/native thiol and disulphide/total thiol in the AA group. In the stepwise regression model, risk factors as disulphide/native thiol (OR = 1.368;p = 0.018 ) and CRP (OR = 1.635;p = 0.003 ) were determined as predictors of perforated appendicitis compared to the nonperforated group. Conclusion . This is the first study examining the thiol/disulphide homeostasis as a diagnostic aid in AA and establishing thiol/disulphide homeostatis balance shifted towards the disulphide formation due to thiol oxidation. Further studies are needed to optimize the use of this novel oxidative stress marker in AA.